Environmental exposure to benzene: evaluation of urinary S-PMA and polymorphism (CYP2E1-1293G>C and NQO1 609C>T) in Campos Elíseos residents, Duque de Caxias, Rio de Janeiro State, Brazil - Cristiane Barata Silva; Caroline de Lima Mota; Yasmin Rocha Almeida; Vanessa Emídio; Antonio Sergio A. Fonseca; Simone Mitri; Josino Costa Moreira
Benzene is one of the most important substances for assessment, due to its significant use, the environmental contamination resulting from its emission and the effects on human health. It is classified by the International Agency for Research on Cancer (IARC) as a known carcinogen to humans (group 1) and associated with the development of leukemia. In general, the population is exposed to this substance by inhaling contaminated air, which varies according to the location and intensity of its potential sources. The petrochemical industry is one of the most important sources of this compound. The municipality of Duque de Caxias, specifically the Campos Elíseos district, in Rio de Janeiro State, Brazil, houses the Industrial Complex of Campos Elíseos (PICE), a grouping of over 25 industries, which includes the second largest oil refinery in Brazil. Environmental contamination from the PICE has been recognized, but there is a lack of studies concerning its impact on the health of the surrounding population. S-phenylmercapturic acid (S-PMA) concentrations ranging from 0.80 to 8.01μg.g-1 creatinine were observed in the local population, apparently related to hematological changes also observed in exposed population. The quantifiable presence of urinary S-PMA from the benzene metabolism is associated with the fact that 60% of the participants present specific hematological changes, which may be due to the environmental benzene exposure. The allele and genotype frequencies of the CYP2E1 and NQO1 enzymes observed in the study population were similar to those reported in other studies. The presence of the variant allele in the NQO1 genotype may be a risk factor for the observed hematological changes.